Emotion and Figurative Language in Taylor Swift’s Selected Songs - Dewi, Ni Nengah Wulan Anggita; Afrianto, Afrianto (JELITA, 2026)
This research explores the connection between symbolic language and how emotions are portrayed in Taylor Swift’s selected songs: The Prophecy and The Smallest Man Who Ever Lived. Based on a descriptive qualitative approach, this investigation aims to explore how rhetorical devices, including metaphors, personification, irony, and hyperbole, serve as methods for conveying complex emotional states. The results suggest that within "The Prophecy," Swift utilizes metaphors, religious references, and reiteration to illustrate feelings of hopelessness, powerlessness, and acceptance of destiny. In contrast, "The Smallest Man Who Ever Lived" depends on the use of irony, overstatement, and explicit descriptions to convey sentiments of treachery, fury, and personal agency. These patterns of figurative speech demonstrate a shift from a state of weakness to one of resilience, indicating that Swift's songwriting leverages symbolic communication not simply to outline feelings but also to represent the development of emotional change in itself. The research determines that the integration of the psychological study of emotions and the linguistic study of figurative language allows for a more profound comprehension of how current songwriters generate significance and emotional impact through innovative lyrical composition.